Development of a Blended Learning Model on Anatomy and Physiology for Professional Nurses by Boromarajonani College of Nursing, Suphanburi, Thailand - P., Poltana; S., Voraroon; W., Khumsuk; A., Phosuwan; D, Panasan; C., Sattayarom (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research were to: 1) study basic information, opinions and needs for blended learning in anatomy and physiology study for professional nurses 2) study the development of the blended learning model for anatomy and physiology for professional nurses 3) propose an experiment for the use of the blended learning model for anatomy and physiology study for professional nurses 4) assess and revise the blended learning model for anatomy and physiology study for professional nurses. The researcher applied research and development rules and procedures and studied data systematically in order to construct the knowledge rehabilitation model for anatomy and physiology for professional nurses. The researcher applied blended research procedures by using qualitative research and quantitative research. The model was aimed at developing the knowledge of professional nurses working in hospitals. Data were collected from professional nurses who gave cooperation to participate in the research, divided into three sets as follows: Set 1: 15 people (Pilot Group 1), Set 2: 40 people (participants) and Set 3: 15 people (Pilot Group 2). Content analysis was conducted following the principles for synthesis, analysis, thinking and interpretation and statistical analysis was conducted with description of individual factors and paired sample test statistical analysis with reliability at 95% (α = 0.05). The finding was showed professional nurses in three set who participated in the learning model had higher knowledge levels post-learning with statistical significance at 0.05. This means that the model can increase knowledge in anatomy and physiology in professional nurses and the satisfaction. Hence, indicating that the aforementioned modal is suitable for professional nurses, who want to use it to develop their anatomy and physiology knowledge.